Evaluasi Kepatuhan Terapi Obat pada Pasien Diabetes Melitus di Rawat Jalan RSUP Fatmawati - Rahmawati, Intan Rizqi; Dwi Yulianti (Jurnal Farmasi Klinik Best Practice, 2024)
Patient compliance in carrying out treatment has an important role in the success of treatment. Therefore, researchers need to evaluate compliance with diabetes mellitus medication use. This research is a cross-sectional observational study with prospective data collection. The research was conducted at the Outpatient Clinic of Fatmawati Hospital in September 2023 – November 2023 using the MMAS-8 method on 57 patients. From the results, it is known that there is a significant relationship between level of education, medical therapy, disease complications, behaviour of health workers, comorbidities and Hba1c on the level of patient compliance. The outcome of the study showed patients with a high level of compliance is 42.1% and a low level of compliance is 47.4%. Patients with high compliance had 38.6% polypharmacy in their medication therapy; had disease complications 33.3%; felt that the behaviour of health workers was friendly 42.1%; have no comorbidities 22.8%; and controlled HbA1C 40.3%.